Credit Worthy : ESG Factors and Sovereign Credit Ratings - Gratcheva, Ekaterina M.; Gurhy, Bryan; Skarnulis, Andrius; Stewart, Fiona E.; Wang, Dieter (World Bank, Washington, DC, 2022)
The increasing role of the financial sector in the move toward a more sustainable economic model continues apace. The Coronavirus (COVID-19) shock shone a light on the need for all society to correct course, and the financial sector is responding. The pace of environmental, social, and governance (ESG) integration into investment decisions, which has become the prevalent form of sustainable finance, continues to accelerate. These developments reflect changing societal perspectives that challenge the traditionally ingrained investment approaches that have evolved over many decades. Against this backdrop, various financial sector stakeholders continue to evaluate how their role, products, and tools should adapt to this evolving landscape. This paper focuses on sovereign credit ratings and empirically assesses how broad sovereign ESG factors as well as the ESG factors specific to a country’s national wealth and management of risks and opportunities related to so-called stranded assets like fossil fuel resources are manifested in sovereign credit rating assessments.